Delaktighet i dagliga aktiviteter hos personer med stroke - Hedquist, Daniel (2015)
Participation in daily activities in people with strokeDelaktighet i dagliga aktiviteter hos personer med strokeMagisterexamensarbete 15hp, Luleå tekniska universitet, institutionen för hälsovetenskap,2015.AbstractParticipation in people with stroke is highlighted in this study based on people's experiences of participation in their daily activities. Occupational therapists play an important role in the rehabilitation of people with stroke, this by assessing and participate in the treatment of people who have difficulties to participate and perform activities. A better understanding of people's experiences of part-icipation in their lives, can contribute to the design of rehabilitation and actions that are relevant to these persons participation. The purpose of this study was to describe the experience of partici-pation in daily activities in people with stroke who received outpatient rehabilitation. The author used a qualitative approach and interviewed people with stroke from three municipalities in northern Sweden, an interview guide with semi structured questions were used during data collection. Data were analyzed by content analysis and gave five categories: “The importance of engagement to experience participation”, The importance of participation in their own training and rehabi-litation”, “Opportunities for participation and performance of daily activities”, “Adapting to new conditions needed to experience participation”, “Barriers and support in the environment is of importance for participation”. The results indicate many aspects of the participants' experiences of participation in their daily activities. The study shows that knowledge is needed regarding participation in daily activities in people with stroke. This knowledge will be of value in the context of medical care and rehabilitation, as well as for other actors and contexts that are relevant for these persons. Validerat; 20150625 (global_studentproject_submitter)